Nitrogen recovery and nitrous oxide (N2O) emissions from aquaponic systems: Influence of plant species and dissolved oxygen. (October 2018) - Wongkiew, Sumeth; Popp, Brian N.; Khanal, Samir Kumar
Abstract: Aquaponics recycles nitrogen from nitrogen-rich aquaculture effluent into organic crops (fish and vegetables/fruits) in hydroponic grow beds. Fundamental understanding of nitrogen transformations in aquaponics is critically important to improve nitrogen use efficiency (NUE) within aquaponics systems and to reduce release of environmentally harmful effluent and gases. This study elucidated nitrogen transformations in floating-raft aquaponic systems using four plant species, namely lettuce ( Lactuca sativa longifolia cv . Jericho ), pak choi ( Brassica rapa L. Chinensis ), tomato ( Lycopersicum esculentum ), and chive ( Allium schoenoprasum L.). Using nitrogen mass balance and 15 N labeled nitrogen species, it was found that nitrate was the primary form of nitrogen assimilated by plants. Nitrification and denitrification occurred simultaneously in the aquaponic system, resulting in an inevitable nitrogen loss (22.3–29.3% of nitrogen input). Nitrogen loss via nitrifier denitrification (33.7–55.3%), which was stimulated by low dissolved oxygen (DO) levels (∼3.8 mg/L), and denitrification occurred simultaneously. Moreover, nitrogen loss from the aquaponic system in the form of nitrous oxide (N2 O), a potent greenhouse gas, accounted up to 0.72–1.03% of the nitrogen input. Aerating biofilters to prevent the formation of anoxic zones reduced total nitrogen loss but did not affect N2 O emission. This study suggests that increasing DO concentrations only by aeration does not improve NUE and reduce N2 O emission simultaneously. Graphical abstract: Highlights: Aquaponics recovered nitrogen from aquaculture effluent via nitrate assimilation. The highest NUE (44.0%) was found in tomato, the fastest-growing plant. High DO levels but not plant species reduced total nitrogen loss from aquaponics. Nitrogen loss occurred via denitrification and nitrifier denitrification. Aerating biofilters (anoxic environment) did not reduce N2 O emissions.